Avaliação das condições higiênico-sanitárias e de boas práticas em matadouro-frigorífico na região oeste do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Brazil is a big world producer of animal protein and has at the domestic market the main destination of his production, which in the year of 2010 was estimated in 24.5 millions of tons, being that 75 % of this production is consumed internally in the country. Nowadays, the consumers are increasingly interested in food quality that they are consuming, specially sanitary-hygienic quality and don’t care about pay a bit more to acquire better quality products, moreover, the supervisory organs are increasingly stricter and for a quality assurance of a food, the production process thereof, should be conducted in sanitary-hygienic conditions and appropriate good practices to provide safe food. This study aimed the evaluation of sanitary-hygienic conditions and good practices in a refrigerator of west border of Rio Grande do Sul, under the supervision of the municipal inspection, in accordance with check list. For the evaluation of sanitary-hygienic and good practices of the establishment were realized three visits with the application of a check list suggested by Saccol; Stangarlin; Hecktheuer (2012) based on Ordinance n° 368 de 4 September 1997, of the MAPA with observation in loco of constants variations of the check list. With the results obtained, it can be observed that the refrigerator has 87,21 % of adequacies, obtained according to the amount of suitable items, a rating "Good" of adequacy about the good practices. So, the inadequacies observed could be avoided if there was a control tool of quality implemented. The application of a check list shows up a useful tool for checking requirements resulting from facilities, equipment, operations and handlers, facilitating the identification of inadequacies and adjustments to improve the production process and guarantee the food security of their consumers.
Keywords: Abate; Check list; Carne; Qualidade; Slaughter; Checklist; Meat; Quality; CNPQ::CIENCIAS AGRARIAS